Cheating in primary school: Experimental evidence on ego-depletion and individual factors - Tamás Keller; Hubert János Kiss; Szabolcs Számadó (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We contribute to the experimental literature on primary school students' cheating behavior by studying i) how cheating is influenced by ego depletion; ii) how it correlates with different individual factors. We carried out a large-scale, pre-registered experiment in the field of 28 Hungarian primary schools (126 classrooms) on a voluntary subsample of 1,143 students at grade levels 4 to 8. Students' cheating behavior was measured by the incentivized dice-roll experiment. We find suggestive evidence that our light-touch treatment on ego-depletion increased students' deceptive behavior. Cheating behavior correlated weakly with students' individual characteristics. In a multivariate context controlling for between-classroom differences, we document that students' cognitive ability correlated negatively, while their age positively, with their cheating behavior. We found students' social context (their classroom belonging) as a more decisive determinant of students' cheating behavior than individual characteristics.
Keywords: A13; C91; D91; 330; honesty; cheating; individual factors; ego depletion; dice-roll exercise; pre-registered experiment